Introduction: Language, Structure and Agency: Optimising Media Diversity in Africa Using the Indigenous Languages - Chibita, Monica B.; Salawu, Abiodun (Palgrave Macmillan, London, 2016)
Language plays a crucial role in the media as a key public domain, to the extent that the languages people use in the media determine their chances of getting heard. However, there are numerous forces determining which languages are used in the public domain and the hierarchy of their deployment. This point has been debated extensively in the literature of language ideology. In her seminal work in this area, Woolard (1992, pp. 235–236), for instance, suggests that to the extent that language is the vehicle of large proportions of media content, it is linked to expression and to power. According to Woolard, “language stands in dialectical relation with, and thus significantly influences, social, discursive and linguistic practices”. There also exists a dialectical relationship between language attitudes and the roles different languages are assigned in the public domain. Because of the important role of language, this relationship constitutes an important issue for discussion in the context of the media’s role in inclusion and exclusion and in the overall democratisation project in Africa. Political economy scholars have for over two decades made the same point about the relationship/s between language, diversity, expression and democracy (see, for instance Golding and Murdock 1991; Goldsmith Media Group 2000; Gurevitch 2000; McChesney 2000; Bagdikian 2014).
Keywords: Language Policy; Political Participation; Indigenous Language; Cultural Expression; African Language